Porous carbon microsphere for silicon-carbon negative electrode as well as preparation method and application of porous carbon microsphere
By using porous carbon microspheres as the carrier of silicon carbon negative electrode material, the problem of degradation of circulation performance caused by volume expansion of silicon materials in the prior art is solved, and a more uniform stress and higher strength are achieved, which significantly improves the circulation performance and life of the battery.
Patent Information
- Application Number
- CN202311264096.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-04
AI Technical Summary
Among the existing silicon-carbon negative electrode materials, the irregular granular structure and low strength of porous carbon are difficult to effectively solve the problem of volume expansion of silicon materials during charging and discharging, resulting in a degradation of cycling performance.
Porous carbon microspheres are used as the negative electrode material support, and the inside is a uniform and dense microporous structure with a microporosity of 50-99%, so as to reduce the size of silicon particles and improve the circulation performance of the negative electrode.
By using porous carbon microspheres, the silicon carbon negative electrode material is subjected to more uniform force and has higher strength during charging and discharging, avoiding the fragmentation and fall of silicon particles, and significantly improving the circulation performance and battery service life.
Smart Images

Figure BDA0004474301500000201 
Figure BDA0004474301500000211 
Figure BDA0004474301500000251
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of silicon-carbon negative electrodes, and in particular to a porous carbon microsphere for silicon-carbon negative electrodes, a preparation method and an application thereof. Background Art
[0002] With the implementation of the global carbon peak and carbon neutrality strategies, energy storage batteries represented by lithium-ion batteries are the future development direction in the field of power and energy storage. At present, the negative electrode of commercial lithium-ion batteries is mainly graphite-based materials. According to the lithium storage mechanism of LiC6 between graphite layers, its theoretical specific capacity is only 372mAh / g, and there is very limited room for improvement. The raw materials of silicon-based negative electrodes are mainly composed of silicon materials and graphite. Silicon alloys with lithium at room temperature, with a theoretical specific capacity of 4200mAh / g, which is more than 10 times that of current graphite negative electrode materials. It is one of the lithium battery negative electrode materials with great application prospects.
[0003] Different from the intercalation mechanism of graphite, silicon crystals present a three-dimensional phase structure of covalent tetrahedrons, and charge and discharge by forming Li-Si alloy with lithium. The volume expansion rate of Li-Si alloy can reach 300%-400%. When discharging, the lithium ions will escape and form gaps. The obvious change in volume will generate strong stress, causing the silicon particles to break and fall off from the electrode sheet, causing a sharp decline in capacity and reducing the cycle life.
[0004] The existing porous carbon used in silicon-carbon negative electrodes is mostly irregular granular structure, with a high proportion of large pores inside the particles and poor strength of porous carbon. It is difficult to solve the problem of silicon expansion, which in turn affects the technical problem of the cycle performance of silicon-carbon negative electrodes. Summary of the invention
[0005] In view of the above problems, the present application provides a porous carbon microsphere for silicon-carbon negative electrode, the porous carbon microsphere structure is evenly stressed and retains its strength to the greatest extent. The porous carbon microsphere has a uniform and dense microporous structure with a microporosity of 50-99%, so the size of silicon can be reduced to the greatest extent and its volume expansion can be limited, thereby improving the cycle performance of the silicon-carbon negative electrode.
[0006] The specific technical solutions of this application are as follows:
[0007] 1. A porous carbon microsphere for a silicon-carbon negative electrode, wherein the microsphere is spherical or nearly spherical, and the microporosity of the microsphere is 50-99%.
[0008] 2. The porous carbon microspheres according to item 1, wherein the pore volume of the microspheres is 0.1-1.5 cm 3 / g, micropore volume is 0.2-1.5cm 3 / g.
[0009] 3. The porous carbon microspheres according to item 1 or 2, wherein the specific surface area of the microspheres is 700-3000m 2 / g.
[0010] 4. The porous carbon microspheres according to any one of items 1 to 3, wherein the particle size Dv50 of the microspheres is 1-10 μm, and Dv100 is less than 30 μm.
[0011] 5. A method for preparing porous carbon microspheres for silicon-carbon negative electrode, comprising:
[0012] The carbon source is polymerized to obtain a carbon microsphere precursor;
[0013] The carbon microsphere precursor is subjected to carbonization reaction and activation reaction to obtain porous carbon microspheres.
[0014] 6. The method according to item 5, wherein the carbon source is selected from one or more of phenolic resin, furan resin, furfural resin, lignin, cellulose, starch, pentose, hexose, molasses, asphalt, mesophase microspheres and starch.
[0015] 7. The method according to item 5 or 6, wherein the polymerization is selected from one of emulsion polymerization, thermal polycondensation, dehydration polymerization, mechanical granulation, spray granulation and hydrothermal carbonization.
[0016] 8. The method according to any one of items 5-7, wherein the temperature of the carbonization reaction is 500-1000°C, and / or the time of the carbonization reaction is 0.5-5h.
[0017] 9. The method according to any one of items 5 to 8, wherein the temperature of the activation reaction is 700-1000° C., and / or
[0018] The activation reaction time is 0.5-2h, and / or
[0019] The activating agent used in the activation reaction is selected from one or more of potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate and sodium bicarbonate.
[0020] 10. The method according to any one of items 5-9, wherein the porous carbon microspheres are the porous carbon microspheres according to any one of items 1-4.
[0021] 11. Use of the porous carbon microspheres described in any one of items 1 to 4 or the porous carbon microspheres prepared by the method described in any one of items 5 to 10 in silicon-carbon negative electrode materials.
[0022] 12. A silicon-carbon negative electrode material, prepared by a method comprising the following steps:
[0023] The porous carbon microspheres described in any one of items 1 to 4 or the porous carbon microspheres prepared by the method described in any one of items 5 to 10 are used as carriers to deposit silicon to obtain a silicon-carbon negative electrode material.
[0024] 13. The silicon-carbon negative electrode material according to item 12, wherein the silicon deposition is obtained by adsorption, decomposition and deposition of silicon-containing gas in the pores of porous carbon microspheres.
[0025] 14. The silicon-carbon negative electrode material according to item 13, wherein the silicon-containing gas is silane or methylsilane, and / or
[0026] The processing temperature during silicon deposition is 300-900°C, and / or
[0027] The processing time of the silicon deposition is 1-24 hours, and / or
[0028] Calculated by mass percentage in the silicon-carbon negative electrode, silicon accounts for 20-75%.
[0029] 15. A method for preparing a silicon-carbon negative electrode material, comprising:
[0030] The porous carbon microspheres described in any one of items 1 to 4 or the porous carbon microspheres prepared by the method described in any one of items 5 to 10 are used as carriers to deposit silicon to obtain a silicon-carbon negative electrode material.
[0031] 16. The method according to item 15, wherein the silicon deposition is obtained by adsorption, decomposition and deposition of silicon-containing gas in the pores of porous carbon microspheres.
[0032] 17. The method according to item 16, wherein the silicon-containing gas is silane or methylsilane, and / or
[0033] The processing temperature during silicon deposition is 300-900°C, and / or
[0034] The processing time of the silicon deposition is 1-24 hours, and / or
[0035] Calculated by mass percentage in the silicon-carbon negative electrode, silicon accounts for 20-75%.
[0036] 18. Use of the silicon-carbon negative electrode material described in any one of items 12 to 14 or the silicon-carbon negative electrode material prepared by the method described in any one of items 15 to 17 in lithium-ion batteries.
[0037] 19. A lithium-ion battery comprising the silicon-carbon negative electrode material described in any one of items 12 to 14 or the silicon-carbon negative electrode material prepared by the method described in any one of items 15 to 17.
[0038] Effects of the Invention
[0039] The porous carbon microspheres described in the present application have a microporous structure of 50-99% inside, which is conducive to the adsorption, cracking and deposition of gas-phase silicon in the micropores and reduces the size of silicon particles, thereby forming a silicon-carbon negative electrode material;
[0040] Compared with granular materials, the porous carbon microspheres described in the present application are more uniform in force direction when silicon expands, have higher strength, are not easily broken due to silicon expansion, and are similar to the nearly spherical graphite material in the negative electrode of lithium batteries;
[0041] The particle size Dv50 of the porous carbon microspheres described in the present application is 1-10 μm, and Dv100 is less than 30 μm, and the particle size range thereof matches that of the negative electrode material of a lithium battery. DETAILED DESCRIPTION
[0042] The embodiments described below are described in detail for the present application. Although specific embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.
[0043] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the functional differences of components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present application, but the description is based on the general principles of the specification and is not intended to limit the scope of the present application. The scope of protection of the present application shall be determined by the attached claims.
[0044] The following embodiments of the present application are only used to illustrate the specific embodiments of the present application, and these embodiments cannot be understood as limiting the present application. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present application are deemed to be equivalent replacement methods and fall within the scope of protection of the present application.
[0045] The specific embodiments of the present application will be described in more detail below. However, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to enable the scope of the present application to be fully communicated to those skilled in the art.
[0046] As used in this specification, "a" or "an" may mean one or more. As used in the claims, when used with the word "comprising", the word "a" or "an" may mean one or more than one.
[0047] The term "or" is used in the claims to mean "and / or" unless explicitly stated to refer only to alternatives or the alternatives are mutually exclusive, although the present disclosure supports a definition referring only to alternatives and "and / or." As used herein, "another" may mean at least a second or more.
[0048] In this application, "pore volume" refers to the volume of all pores in a material sample, also generally referred to as pore capacity, and is usually expressed in ml / g. The adsorption behavior of a pore varies depending on the pore diameter. The pore size (pore width) defined by IUPAC is divided into: micropores <2nm; mesopores 2-50nm; macropores 50-7500nm; megapores >7500nm (mercury can enter under atmospheric pressure). In this application, "pore volume" refers to the volume of all pores in a material sample, which can be micropores, mesopores, macropores, or megapores.
[0049] In this application, "micropore volume" refers to the volume of pores with a pore size (pore width) less than 2 nanometers. Some microporous materials can be used to adsorb gases because they can selectively adsorb molecules. Generally speaking, the larger the total pore volume, the larger the micropore volume will be.
[0050] In the present application, the pore volume and micropore volume of the porous carbon microspheres can be detected by any method known to those skilled in the art, and those skilled in the art can select the method based on their needs.
[0051] For example, the pore volume and micropore volume of the porous carbon microspheres can be detected by nitrogen adsorption desorption method, mercury intrusion method, bubble pressure method, scanning electron microscopy, microscopy, optical projection method, laser scanning method, X-ray diffraction method, etc., preferably by nitrogen adsorption desorption method. Those skilled in the art can select the above or any other detection method in the art based on the actual situation based on the detection conditions and the instruments used.
[0052] In this application, "particle size" refers to the size of the particles, also known as "particle size" or "diameter". When a certain physical property or physical behavior of the measured particle is closest to a homogeneous sphere (or combination) of a certain diameter, the diameter (or combination) of the sphere is taken as the equivalent particle size (or particle size distribution) of the measured particle. The measurement of particle size can be detected by optical methods, laser particle size analyzer, scanning electron microscope (SEM), transmission electron microscope (TEM) and other methods, preferably by laser particle size analyzer method. Those skilled in the art can select the above or any other detection method in the field based on the actual situation based on the detection conditions and the instruments used.
[0053] In this application, "specific surface area" refers to the total area per unit mass of a material. The unit is m 2 / g. It usually refers to the specific surface area of solid materials, such as powders, fibers, particles, flakes, blocks and other materials.
[0054] The main methods for testing specific surface area are continuous flow method (i.e. dynamic method) and static volumetric method. The dynamic method is to place the powder sample to be tested in a U-shaped sample tube, so that a mixed gas containing a certain proportion of adsorbent flows through the sample, and the adsorption amount of the adsorbent molecule (N2) of the sample to be tested is determined according to the change in gas concentration before and after adsorption. Commonly used principles include direct comparison method and multi-point BET method. The static method is divided into gravimetric method and volumetric method according to the different methods for determining the adsorption amount. The gravimetric method is to determine the adsorption amount of the adsorbent molecule (N2) of the sample to be tested according to the change in sample weight before and after adsorption; the volumetric method is to place the powder sample to be tested in a closed test tube-shaped sample tube of a certain volume, inject a certain pressure of adsorbent gas into the sample tube, and determine the adsorption amount of the adsorbent molecule (N2) of the sample to be tested according to the pressure or weight change before and after adsorption. The purpose of both the dynamic method and the static method is to determine the adsorption amount of the adsorbent gas. After the adsorption amount of the adsorbent gas is determined, the specific surface area of the powder to be tested can be calculated by the adsorption amount of the adsorbent molecule.
[0055] For materials with regular shapes, their specific surface area can be calculated by geometric methods. For common irregular-shaped substances, their specific surface area is usually calculated based on model assumptions. In theory, the specific surface area S can be calculated by the number of molecules of known size (usually assumed to be spherical or cubic) occupying the surface of the substance. At present, the specific surface area of the material is usually conveniently determined based on the model assumptions through adsorption isotherms. Depending on the model assumptions adopted, the methods that can be used to calculate the specific surface area of the material mainly include: Langmuir method, BET method, B point method, empirical mapping method, BJH method, DR method and NLDFT method. Among them, Langmuir method and BET method are the main methods.
[0056] In this application, "microporosity" refers to the ratio of the micropore volume of pores in a material to the pore volume. Before calculating the microporosity, the micropore volume and pore volume of the material need to be measured first, microporosity = micropore volume / pore volume × 100%.
[0057] In the present application, "current collector" refers to a structure or part that collects current and is made of a conductive material. The size of the current collector can be determined according to the use of the capacitor (or battery). For example, if it is used in a large supercapacitor requiring high energy density, a current collector with a large area can be used. There is no special restriction on the thickness of the current collector. The thickness of the current collector is usually about 0.1 to 1000 μm, preferably about 1 to 100 μm. There is no special limitation on the shape of the current collector. There is no special restriction on the material constituting the current collector. For example, a metal, a conductive polymer material, or a resin obtained by adding a conductive filler to a non-conductive polymer material can be used. Specifically, as metals, aluminum, nickel, iron, stainless steel, titanium and copper can be listed. In addition, it is preferred to use a clad material with aluminum, a clad material of copper and aluminum, or a plating material of a combination of these metals. In addition, it can also be a foil formed by coating aluminum on the metal surface. Among these, aluminum, stainless steel, copper, and nickel are preferred from the viewpoints of electron conductivity, battery operating voltage, and adhesion of the negative electrode active material to the current collector when sputtering is used.
[0058] In this application, "first coulombic efficiency" refers to the efficiency of electron transfer in an electrochemical reaction. It refers to the ability of electrons to reach the reactants in the solution from the electrode in an electrochemical reaction, which can be used to evaluate the efficiency and feasibility of the electrochemical reaction. First coulombic efficiency = actual charge transfer amount / theoretical charge transfer amount × 100%. Among them, the actual charge transfer amount refers to the amount of charge actually transferred in the electrochemical reaction, and the theoretical charge transfer amount refers to the amount of charge that should theoretically be transferred in the electrochemical reaction. The value of the first coulombic efficiency is usually between 0% and 100%. If the value of the first coulombic efficiency is close to 100%, it means that the efficiency of the electrochemical reaction is very high and the reaction is feasible. If the value of the first coulombic efficiency is very low, it means that the efficiency of the electrochemical reaction is very low and the reaction is not feasible.
[0059] In this application, "discharge capacity" refers to the amount of electricity that a battery can discharge from full to empty. It is usually expressed in units of "ampere-hour (Ah)" or "milliampere-hour (mAh)". For example, a 1000mAh battery means that the battery can be discharged at a current of 1A within one hour. The "first-cycle discharge capacity", also known as the first discharge gram capacity, refers to the amount of electricity that a battery can release in the first charge and discharge cycle. It is one of the important indicators of battery quality because it directly affects the battery's service life and performance. If the first discharge gram capacity is low, the actual service life of the battery will be reduced accordingly.
[0060] The electrochemical reaction principle of silicon-lithium batteries is that when the battery is charged, lithium ions will escape from the positive electrode (cathode) material and enter the electrolyte, move from the electrolyte to the negative electrode (anode) material, and embed into the lattice inside the negative electrode (anode) silicon crystal, causing a large expansion. At the same time, the silicon atoms on the silicon negative electrode (anode) will form chemical bonds with lithium to form silicon-lithium compounds. During the discharge process, the lithium ions in the compound escape from the lattice and move again to the positive electrode (cathode) material, and the silicon is restored to its original silicon material.
[0061] However, the dramatic volume effect of silicon materials during the lithium insertion / extraction process limits their practical application. Drastic volume changes will cause the electrode material to rapidly mechanically pulverize and gradually detach from the current collector, resulting in a rapid decrease in capacity. At the same time, it will also cause the solid electrolyte interface (SEI) on the surface of the material to be continuously destroyed and reconstructed, resulting in continuous lithium ion loss. A good solution to the above problems is to compound with elastic conductive materials, so that the composite of silicon and carbon materials becomes an ideal choice for lithium-ion battery anodes.
[0062] Porous carbon microspheres
[0063] The inventors have found that when the pores inside the carbon microspheres used as negative electrodes meet certain conditions, they can provide more space for the volume change of the silicon material and prevent the mechanical pulverization and detachment of the silicon material, thereby improving the performance of the battery using the carbon microspheres as the electrode active material.
[0064] Therefore, in one aspect, the present application provides a porous carbon microsphere for silicon-carbon negative electrode. The microsphere is spherical or nearly spherical, and the microporosity of the microsphere is 50-99%.
[0065] For example, the microporosity of the microspheres can be 50%, 60%, 70%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, etc.
[0066] In one embodiment of the present application, the pore volume of the microspheres is 0.5-1.5 cm 3 / g, for example, the pore volume of the microspheres may be 0.1 cm 3 / g, 0.2cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.5cm 3 / g, 0.55cm 3 / g, 0.6cm 3 / g, 0.65cm 3 / g, 0.7cm 3 / g, 0.75cm 3 / g, 0.8cm 3 / g, 0.85cm 3 / g, 0.9cm 3 / g, 0.95cm 3 / g, 1.0cm 3 / g, 1.05cm 3 / g, 1.10cm 3 / g, 1.15cm 3 / g, 1.20cm 3 / g, 1.30cm 3 / g, 1.40cm 3 / g, 1.50cm 3 / g, etc.
[0067] In one embodiment of the present application, the micropore volume of the microsphere is 0.1-1.5 cm 3 / g, for example, the micropore volume of the microspheres may be 0.2 cm 3 / g, 0.3cm 3 / g, 0.4cm 3 / g, 0.45cm 3 / g, 0.5cm 3 / g, 0.55cm 3 / g, 0.6cm 3 / g, 0.65cm 3 / g, 0.7cm 3 / g, 0.75cm 3 / g, 0.8cm 3 / g, 0.85cm3 / g, 0.9cm 3 / g, 0.95cm 3 / g, 0.99cm 3 / g, 1.0cm 3 / g, 1.05cm 3 / g, 1.10cm 3 / g, 1.15cm 3 / g, 1.20cm 3 / g, 1.30cm 3 / g, 1.40cm 3 / g, 1.50cm 3 / g, etc.
[0068] The pore volume and micropore volume of the microspheres can be measured by nitrogen adsorption and desorption method, which can be measured according to GB / T19587-2017.
[0069] The microporosity of the micropores is calculated using the micropore volume and the pore volume, and the calculation formula is as follows: microporosity=micropore volume / pore volume×100%.
[0070] In one embodiment of the present application, the specific surface area of the microspheres is 700-3000m 2 / g, for example, the specific surface area of the microspheres can be 700m 2 / g、800m 2 / g、900m 2 / g、1000m 2 / g, 1050m 2 / g、1100m 2 / g, 1150m 2 / g、1200m 2 / g, 1250m 2 / g、1300m 2 / g, 1350m 2 / g、1400m 2 / g, 1450m 2 / g、1500m 2 / g, 1550m 2 / g、1600m 2 / g, 1650m 2 / g、1700m 2 / g, 1750m 2 / g、1800m 2 / g, 1850m 2 / g、1900m 2 / g, 1950m 2 / g, 2000m 2 / g, 2050m 2 / g, 2100m 2 / g, 2150m 2 / g, 2200m 2 / g, 2300m 2 / g, 2400m 2 / g, 2500m 2 / g、2600m 2 / g, 2700m 2 / g、2800m 2 / g、2900m 2 / g、3000m 2 / g, etc.
[0071] In the present application, the specific surface area can be measured by nitrogen adsorption and desorption method, which can be measured according to GB / T19587-2017.
[0072] In one embodiment of the present application, the particle size Dv50 of the microspheres is 1-10 μm, and Dv100 is less than 30 μm. For example, Dv50 can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, etc.
[0073] The Dv100 of the microspheres can be, for example, 29μm, 28μm, 27μm, 26μm, 25μm, 24μm, 23μm, 22μm, 21μm, 20μm, 19μm, 18μm, 17μm, 16μm, 15μm, 14μm, 13μm, 12μm, 11μm, 10μm, 9μm, 8μm, 7μm, 6μm, 5μm, etc.
[0074] In this application, Dv50 refers to the particle size corresponding to when the cumulative particle size distribution number of a sample reaches 50%. Its physical meaning is that particles with a particle size smaller than it account for 50% of the total volume. Similarly, Dv100 refers to the particle size corresponding to when the cumulative particle size distribution number of a sample reaches 100%. Its physical meaning is that particles with a particle size smaller than it account for 100% of the total volume. In this application, the particle sizes Dv50 and Dv100 of the microspheres can be measured using a laser particle size analyzer, for example, according to GB / T24533-2019.
[0075] In addition, the inventors have also found that the activated carbon microspheres of the present application can be easily prepared by the following manufacturing method. Therefore, in another aspect, the present application also provides a method for preparing activated carbon microspheres (the preparation method of the present application), which comprises the following steps:
[0076] Step 1: polymerizing the carbon source to obtain a carbon microsphere precursor;
[0077] Step 2: subjecting the carbon microsphere precursor to carbonization reaction and activation reaction to obtain porous carbon microspheres.
[0078] In one embodiment of the present application, the carbon source is selected from one or more of phenolic resin, furan resin, furfural resin, lignin, cellulose, starch, pentose, hexose, molasses, asphalt, mesophase microspheres, and starch, preferably phenolic resin, lignin, starch, hexose or pentose; preferably, the pentose is xylose and the hexose is glucose.
[0079] In one embodiment of the present application, the polymerization is selected from one of emulsion polymerization, thermal polycondensation, dehydration polymerization, mechanical granulation, spray granulation and hydrothermal carbonization, preferably emulsion polymerization, spray granulation and mechanical granulation.
[0080] In one embodiment of the present application, the temperature of the carbonization reaction is 500-1000° C., preferably 500-650° C., and / or the time of the carbonization reaction is 0.5-5 h, preferably 1-2 h.
[0081] For example, the temperature of the carbonization reaction can be 500°C, 550°C, 600°C, 650°C, 700°C, 800°C, 900°C, 1000°C, etc.; the carbonization reaction time can be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, etc.
[0082] In one embodiment of the present application, the carbonization reaction is carried out in an inert gas, preferably in a nitrogen atmosphere.
[0083] In one embodiment of the present application, the activation reaction is carried out in an inert gas atmosphere such as nitrogen at a temperature of 700-1000° C., preferably 750-800° C., and / or
[0084] The activation reaction time is 0.5-2h, preferably 1.0-1.5h, and / or
[0085] The activator used in the activation reaction is selected from one or more of potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate and sodium bicarbonate, preferably potassium hydroxide or sodium hydroxide.
[0086] For example, the temperature of the activation reaction can be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, 1000°C, etc.
[0087] For example, the activation reaction time can be 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h, etc.
[0088] In one embodiment of the present application, the mass ratio (m 微球前驱体 :m 活化剂 ) is 1:1-4, preferably 1:1.5-2.5. For example, the mass ratio of the microsphere precursor to the activator can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, etc.
[0089] In the present application, since the activation reaction uses a selected activator, by controlling the given ratio of the catalyst to the microsphere precursor, and selecting the temperature and time of the activation reaction, it is possible to obtain carbon microspheres with a given particle size and particle size distribution. And the preparation method of the present application can be used to obtain the desired carbon microspheres with given parameters of the present application, for example, the porous carbon microspheres described in items 1 to 4 of the present application can be obtained by using the preparation method of the present application.
[0090] Silicon Carbon Anode Material
[0091] In one embodiment of the present application, the present application also provides the use of any of the above-mentioned carbon microspheres in silicon-carbon negative electrode materials.
[0092] In one embodiment of the present application, the present application also provides the use of the porous carbon microspheres described in items 1-4 of the application or the porous carbon microspheres obtained by the above preparation method in silicon-carbon negative electrode materials.
[0093] Therefore, in another aspect, the present application also provides a silicon-carbon negative electrode material, which is prepared by a method comprising the following steps: using any of the aforementioned porous carbon microspheres or the porous carbon microspheres prepared by the aforementioned method as a carrier to deposit silicon to obtain the silicon-carbon negative electrode material.
[0094] Preferably, the silicon-carbon negative electrode material uses the porous carbon microspheres of the present application as carriers. In the silicon-carbon negative electrode material, the weight ratio of the porous carbon microspheres of the present application is more than 25%, more than 40%, more than 50%, more than 80%, and preferably 20-75%.
[0095] In this application, for the silicon-carbon negative electrode material, in addition to the porous carbon microspheres of this application, the silicon-carbon negative electrode material may also contain other negative electrode active materials, such as: graphite (natural graphite, artificial graphite, etc.) as highly crystalline carbon, low-crystalline carbon (soft carbon, hard carbon), carbon black (KetjenBlack (registered trademark), acetylene black, channel black, lamp black, oil furnace black, thermal cracking carbon black, etc.), fullerenes, carbon nanotubes, carbon nanofibers, carbon nanobuds, carbon filaments and other carbon materials. In addition, as negative electrode active materials, there can also be listed the simple substances of elements that alloy with lithium such as Si, Ge, Sn, Pb, Al, In, Zn, H, Ca, Sr, Ba, Ru, Rh, Ir, Pd, Pt, Ag, Au, Cd, Hg, Ga, Tl, C, N, Sb, Bi, O, S, Se, Te, Cl, etc., oxides and carbides containing these elements. As such oxides, there can be listed silicon monoxide (SiO), SiO x (0 < x < 2), tin dioxide (SnO2), SnO x (0 < x < 2), SnSiO3, etc. As carbides, there can be listed silicon carbide (SiC), etc. In addition, as negative electrode active materials, there can also be listed metal materials such as lithium metal, lithium-transition metal composite oxides (such as lithium titanate Li4Ti5O 12 ). However, it is not limited to these materials, and traditional well-known materials that can be used as negative electrode active materials for lithium-ion secondary batteries can be used. These negative electrode active materials can be used alone only one kind, or two or more kinds can be used in combination.
[0096] In one embodiment of this application, the method of silicon deposition can be physical vapor deposition (PVD), chemical vapor deposition (CVD), microwave plasma electron cyclotron resonance chemical vapor deposition (MWECRCVD), plasma enhanced chemical vapor deposition (PECVD), etc.
[0097] In one embodiment of this application, the silicon deposition is obtained by the adsorption, cracking and deposition of silicon-containing gas in the pores of the porous carbon microspheres. In some embodiments, the silicon deposition is gas-phase silicon deposition.
[0098] In one embodiment of this application, the silicon-containing gas is silane or methylsilane, and / or
[0099] the treatment temperature during the silicon deposition is 300 - 900 °C, and / or
[0100] the treatment time during the silicon deposition is 1 - 24 h, and / or
[0101] Calculated by the mass percentage in the silicon-carbon negative electrode, silicon is 20 - 75%.
[0102] For example, the processing temperature of the silicon deposition may be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, etc.
[0103] For example, the processing time for the silicon deposition may be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h, etc.
[0104] For example, the mass fraction of silicon can be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, etc., measured by mass percentage in the silicon-carbon negative electrode.
[0105] The present application also provides a method for preparing a silicon-carbon negative electrode material, which comprises using any of the aforementioned porous carbon microspheres or the porous carbon microspheres prepared by the aforementioned method as a carrier to deposit silicon to obtain a silicon-carbon negative electrode material, wherein:
[0106] The silicon deposition is obtained by adsorption, decomposition and deposition of silicon-containing gas in the pores of the porous carbon microspheres.
[0107] The silicon-containing gas is silane or methylsilane, and / or
[0108] The processing temperature during silicon deposition is 300-900°C, and / or
[0109] The processing time of the silicon deposition is 1-24 hours, and / or
[0110] Calculated by mass percentage in the silicon-carbon negative electrode, silicon accounts for 20-75%.
[0111] For example, the processing temperature of the silicon deposition may be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, etc.
[0112] For example, the processing time for the silicon deposition may be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h, 24 h, etc.
[0113] For example, the mass fraction of silicon can be 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, etc., measured by mass percentage in the silicon-carbon negative electrode.
[0114] In the present application, the temperature and time of the silicon deposition reaction and the proportion of silicon in the silicon-carbon negative electrode can be used to obtain a silicon-carbon negative electrode material with given parameters. And the preparation method of the present application can be used to obtain the desired silicon-carbon negative electrode material with given parameters of the present application.
[0115] Battery
[0116] The present application also provides the use of any of the aforementioned silicon-carbon negative electrode materials or the silicon-carbon negative electrode materials prepared by the aforementioned method in lithium-ion batteries.
[0117] Therefore, the present application also provides a lithium-ion battery, which comprises any one of the aforementioned silicon-carbon negative electrode materials or the silicon-carbon negative electrode material prepared by the aforementioned method.
[0118] In one embodiment of the present application, the lithium-ion battery comprises: an electrode, a separator, and an electrolyte, wherein the electrode comprises any one of the aforementioned silicon-carbon negative electrode materials.
[0119] In one embodiment of the present application, the lithium ion battery is prepared by a method in the art, for example, by the following method:
[0120] Any of the aforementioned silicon-carbon negative electrode materials is mixed with SP, SBR, and CMC in a certain mass ratio, and the mixture is mixed into a slurry using a solvent, which is evenly coated on a copper foil and vacuum dried to obtain a battery electrode; then a lithium sheet is used as a counter electrode, a four-component mixed solvent of LiPF6 with a certain molar concentration is used as an electrolyte, and a diaphragm is used to assemble a CR2032 button half-cell in a vacuum glove box.
[0121] The electrode can be manufactured by conventional methods. That is, the silicon-carbon negative electrode material and the conductive agent, as well as the binder and thickener used as needed, can be dry-mixed and formed into a sheet, and the sheet material is pressed on the electrode collector, or the materials are dissolved or dispersed in a liquid medium to form a slurry, and the slurry is applied to the electrode collector and dried, thereby forming an electrode active material layer on the collector, thereby obtaining the electrode.
[0122] In the present application, "conductive agent" means a certain amount of conductive material that is usually added when the electrode is made in order to ensure that the electrode has good charge and discharge performance, so as to reduce the contact resistance of the electrode, accelerate the movement rate of electrons, and effectively increase the migration rate of lithium ions in the electrode material, thereby improving the charge and discharge efficiency of the electrode. It may contain graphene. In addition to the graphene, the conductive agent may also contain any other component that can be used as a conductive agent. For example, it may also contain: metal materials such as copper and nickel; graphite such as natural graphite and artificial graphite; carbon black such as acetylene black; carbon materials such as amorphous carbon such as needle coke, etc. These conductive agents can be used alone, or two or more can be used in combination in any combination and proportion.
[0123] In the present application, the "binder" is used to manufacture the electrode active material layer, and there is no special restriction. In the case of a coating method, any material that can be dissolved or dispersed in the liquid medium used to manufacture the electrode can be used. Specific examples thereof include: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber polymers such as SBR (styrene-butadiene rubber), NBR (nitrile rubber), fluororubber, isoprene rubber, butadiene rubber, and ethylene-propylene rubber; styrene-butadiene-styrene block copolymers; Thermoplastic elastomer-like polymers such as ethylene-propylene-diene terpolymer or its hydrogenation product, EPDM (ethylene-propylene-diene terpolymer), styrene-ethylene-butadiene-ethylene copolymer, styrene-isoprene-styrene block copolymer or its hydrogenation product; soft resin-like polymers such as syndiotactic 1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymer, propylene-α-olefin copolymer; fluorine-based polymers such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, polytetrafluoroethylene-ethylene copolymer; polymer compositions having ion conductivity of alkali metal ions (especially lithium ions), etc. It should be noted that these substances can be used alone or in combination of two or more in any combination and ratio.
[0124] In the present application, the "counter electrode", also called the auxiliary electrode, forms a series circuit with the working electrode and is used to measure the current flowing through the working electrode. It not only plays a conductive role, but also completes another half-reaction. General counter electrodes must meet the following conditions: materials with stable properties, such as platinum (platinum wire, platinum sheet, platinum mesh) or graphite (graphite rods of different diameters); in order to reduce the impact of the polarization of the counter electrode on the working electrode, the resistance of the counter electrode itself should be small and not easy to polarize, and its area is usually required to be larger than the working electrode. In the present application, the battery pole piece prepared as above is the working electrode.
[0125] In the present application, "solvent" is used to form a slurry. As long as it can dissolve or disperse the electrode active material, the conductive agent, the binder, and the thickener used as needed, there is no special restriction on its type, and any solvent in aqueous solvents and organic solvents can be used. As aqueous media, for example, water, mixed media of alcohol and water, etc. can be listed. As organic media, for example, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N, N-dimethylaminopropylamine; ethers such as ether, propylene oxide, tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, dimethylacetamide; polar aprotic solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc. In particular, when an aqueous medium is used, it is preferred to form a slurry using a thickener and a latex such as styrene-butadiene rubber (SBR).
[0126] The separator is usually arranged between the positive electrode and the negative electrode. There is no particular restriction on the material and shape of the separator, and any known separator can be used. For example, a separator made of resin, glass fiber, inorganic material, etc., preferably a porous sheet or non-woven fabric with excellent liquid retention, etc. can be used.
[0127] As materials for resin and glass fiber separators, polyolefins such as polyethylene and polypropylene, aromatic polyamides, polytetrafluoroethylene, polyethersulfone, glass filters, etc. can be used. Among them, glass filters and polyolefins are preferred, and polyolefins are further preferred. The above materials can be used alone, or two or more can be used in combination in any combination and proportion. The separator can be of any thickness, for example, it can be more than 1 μm, preferably more than 5 μm, more preferably more than 8 μm, and usually less than 50 μm, preferably less than 40 μm, and more preferably less than 30 μm. When using porous materials such as porous sheets and non-woven fabrics as separators, the porosity of the separator is arbitrary, for example, it can be more than 20%, preferably more than 35%, more preferably more than 45%, and usually less than 90%, preferably less than 85%, and more preferably less than 75%. The average pore size of the separator is also arbitrary, for example, it can be less than 0.5 μm, preferably less than 0.2 μm, and usually more than 0.05 μm. On the other hand, as inorganic materials, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, sulfates such as barium sulfate and calcium sulfate can be used, and inorganic materials in particle shape or fiber shape can be used. As the form of the diaphragm, a film shape such as non-woven fabric, woven fabric, microporous film, etc. can be used. Among the film shapes, it is preferred to use a film with a pore size of 0.01 to 1 μm and a thickness of 5 to 50 μm. In addition to the above-mentioned independent film shapes, the following diaphragms can also be used: a diaphragm obtained by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin binder. For example, the following can be cited: using fluororesin as a binder, 90% of aluminum oxide particles with a particle size of less than 1 μm form a porous layer on both sides of the positive electrode.
[0128] In one embodiment of the present application, the separator is a polypropylene film.
[0129] The electrolyte solution may be obtained by dissolving a supporting salt (lithium salt) in an organic solvent. Examples of the lithium salt include: LiPF6, LiBF4, LiClO4, LiAsF6, LiTaF6, LiAlCl4, Li2B 10 Cl 10Inorganic acid anion salts such as LiCF3SO3, Li(CF3SO2)2N, Li(C2F5SO2)2N, etc., at least one lithium salt of organic acid anion salts such as LiCF3SO3, Li(CF3SO2)2N, etc. In addition, as the organic solvent, for example, cyclic carbonates such as propylene carbonate (PC) and ethylene carbonate (EC); chain carbonates such as dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC); ethers such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 1,2-dimethoxyethane, 1,2-dibutoxyethane; lactones such as γ-butyrolactone; nitriles such as acetonitrile; esters such as methyl propionate; amides such as dimethylformamide; solvents selected from at least one or a mixture of two or more of methyl acetate and methyl formate, using organic solvents such as aprotic solvents, etc. can be used.
[0130] The electrolyte solution may be formed by dissolving the sodium salt and the above-mentioned additives in a non-aqueous solvent as an organic solvent. There is no particular restriction on the proportion of the additives, but the additives are preferably contained in the non-aqueous electrolyte at a ratio of 0.5 to 10% by volume, more preferably 0.5 to 5% by volume, and further preferably 0.5 to 2% by volume. Examples of the sodium salt include, for example, NaPF6, NaBF4, NaClO4, NaAsF6, NaTaF6, NaAlCl4, Na2B 10 Cl 10 At least one sodium salt in the organic acid anion salts such as inorganic acid anion salts, NaCF3SO3, Na(CF3SO2)2N, Na(C2F5SO2)2N, etc. In addition, as non-aqueous solvent, for example, a non-aqueous solvent consisting of saturated cyclic carbonate, a non-aqueous solvent consisting of saturated cyclic carbonate and chain carbonate can be used. As saturated cyclic carbonate, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) etc. can be listed. In addition, as chain carbonate, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) etc. can be listed. In addition, other non-aqueous solvents may also be included. For example, a solvent selected from the following group or a mixture of two or more thereof may be used: ethers such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 1,2-dimethoxyethane, 1,2-dibutoxyethane; lactones such as γ-butyrolactone; nitriles such as acetonitrile; esters such as methyl propionate; amides such as dimethylformamide; methyl acetate, methyl formate.
[0131] As the electrolyte solution, for example, an aqueous solution containing potassium hydroxide can also be mentioned.
[0132] Examples of the electrolyte include dilute sulfuric acid.
[0133] The separator may be impregnated with the electrolyte solution.
[0134] In one embodiment of the present application, the lithium ion battery is prepared by the following method:
[0135] Any of the aforementioned silicon-carbon negative electrode materials is mixed with SP, SBR, and CMC in a certain mass ratio, and the mixture is mixed into a slurry using a solvent, which is evenly coated on a copper foil and vacuum dried to obtain a battery electrode; then a lithium sheet is used as a counter electrode, a four-component mixed solvent of LiPF6 with a certain molar concentration (EC:DMC:EMC:FEC in a certain mass ratio) is used as an electrolyte, and a diaphragm is used to assemble a CR2032 button half-cell in a vacuum glove box.
[0136] In one embodiment of the present application, the lithium ion battery is prepared by the following method:
[0137] Any of the aforementioned silicon-carbon negative electrode materials is mixed with SP, SBR, and CMC in a mass ratio of 80:10:5:5, and the mixture is mixed into a slurry using ultrapure water as a solvent, and the slurry is evenly coated on a copper foil and vacuum dried at 120°C for 12 hours to obtain a battery electrode; then a lithium sheet is used as a counter electrode, a four-component mixed solvent of LiPF6 with a molar concentration of 1 mol / L (according to the mass ratio of EC:DMC:EMC:FEC=3:4:2:1) is used as an electrolyte, and a polypropylene film is used as a diaphragm to assemble a CR2032 button half-cell in a vacuum glove box.
[0138] In the present application, since a selected silicon-carbon negative electrode material slurry is used in a lithium-ion battery, and a selected electrolyte and a separator are used, a battery with given performance can be obtained by controlling the proportion of the components of the slurry and the proportion of the components of the electrolyte.
[0139] Example
[0140] The present application provides a general and / or specific description of the materials and test methods used in the experiments. In the following examples, unless otherwise specified, % means wt%, i.e., weight percentage. The reagents or instruments used without indicating the manufacturer are all conventional reagent products that can be obtained commercially.
[0141] Example 1
[0142] Example 1-1 Preparation of porous carbon microspheres
[0143] (1) Phenolic resin is prepared by emulsion polymerization to obtain a microsphere precursor with a particle size Dv50 of 7.2 μm. The specific method is as follows:
[0144] Phenol and formaldehyde are mixed at a molar ratio of 1:1.25, and phenol and a catalyst such as potassium hydroxide or ammonia water are mixed at a molar ratio of 1:0.2, and the mixture is reacted at 80° C. for 6 hours to obtain a first mixed solution;
[0145] The first mixed liquid is mixed with soybean oil in a volume ratio of 1:50, and then a non-ionic surfactant such as Span85 or Tween-60 is added with a volume fraction of 0.1 to obtain a second mixed liquid. The second mixed liquid is emulsified according to a conventional method in the art and then reacted at 80° C. for 6 hours to obtain a reaction product. The obtained product is centrifuged and washed with an organic solvent to obtain a microsphere precursor.
[0146] (2) The microsphere precursor is carbonized in an inert gas such as nitrogen at 650°C for 2 hours to prepare carbon microspheres.
[0147] (3) The carbon microspheres are mixed with potassium hydroxide in a ratio of 1:1.5, activated at 800°C for 2h in an inert gas such as nitrogen atmosphere, washed with 3% hydrochloric acid, washed with deionized water to a pH of 5-7, and then heat treated at 800-1000°C for 2h to obtain porous carbon microspheres that can be used for silicon-carbon negative electrodes, wherein the particle size Dv50, pore volume, micropore volume, specific surface area, and microporosity of the porous carbon microspheres are as described in Table 1, wherein the particle size Dv50 and Dv100 of the porous carbon microspheres are determined as follows: using a laser particle size analyzer in accordance with GB / T24533-2019.
[0148] The pore volume, micropore volume and specific surface area are determined by nitrogen adsorption and desorption method according to GB / T19587-2017.
[0149] The microporosity is determined as follows: microporosity = micropore volume / pore volume × 100%.
[0150] Example 1-2 Preparation of porous carbon microspheres
[0151] The difference between Example 1-2 and Example 1-1 is that the porous carbon microspheres and potassium hydroxide are mixed in a ratio of 1:2, and the particle size Dv50, Dv100, pore volume, micropore volume, microporosity and specific surface area of the carbon microspheres are measured according to the method of Example 1-1, and the results are shown in Table 1.
[0152] Example 1-3 Preparation of porous carbon microspheres
[0153] The difference between Example 1-3 and Example 1-1 is that the porous carbon microspheres and potassium hydroxide are mixed in a ratio of 1:3, and the particle size Dv50, Dv100, pore volume, micropore volume, microporosity and specific surface area of the carbon microspheres are measured according to the method of Example 1-1, and the results are shown in Table 1.
[0154] Example 1-4 Preparation of porous carbon microspheres
[0155] (1) Phenolic resin is spray-dried to obtain a microsphere precursor with a particle size Dv50 of 9.6 μm. The specific method is as follows:
[0156] Liquid phenolic resin with a viscosity of 3000-10000 mPa·S enters the spray drying equipment through a feed pump. The feed port temperature of the equipment is 150-200°C, and the discharge port temperature is 70-120°C. Microsphere precursors can be prepared by adjusting the feed speed.
[0157] (2) The microsphere precursor is carbonized in an inert gas atmosphere such as nitrogen at 600°C for 2 hours to prepare carbon microspheres.
[0158] (3) The carbon microspheres are mixed with potassium hydroxide in a ratio of 1:2, activated at 800°C for 2 h in an inert gas such as nitrogen atmosphere, washed with 3% hydrochloric acid, washed with deionized water to a pH of 5-7, and then heat treated at 1000°C for 2 h to obtain porous carbon microspheres that can be used for silicon-carbon negative electrodes. The particle size Dv50, Dv100, pore volume, micropore volume, microporosity and specific surface area of the porous carbon microspheres are determined according to the method described in Example 1. The results are shown in Table 1.
[0159] Example 1-5 Preparation of porous carbon microspheres
[0160] (1) Lignin was dissolved in a sodium hydroxide solution and a microsphere precursor with a particle size Dv50 of 9.4 μm was prepared by spray drying and granulation.
[0161] The preparation method is as follows:
[0162] A lignin solution with a viscosity of 3000-10000 mPa·S is fed into a spray drying device through a feed pump, the feed port temperature is 150-200°C, the discharge port temperature is 70-120°C, and a microsphere precursor can be prepared by adjusting the feed rate.
[0163] (2) The microsphere precursor is carbonized at 650°C for 2 h in an inert gas atmosphere such as nitrogen to prepare carbon microspheres.
[0164] (3) The carbon microspheres are mixed with potassium hydroxide in a ratio of 1:2, activated at 800°C for 2 h in an inert gas such as nitrogen atmosphere, washed with 3% hydrochloric acid, washed with deionized water to a pH of 5-7, and then heat treated at 1000°C for 2 h to obtain porous carbon microspheres that can be used for silicon-carbon negative electrodes. The particle size Dv50, Dv100, pore volume, micropore volume, microporosity and specific surface area of the porous carbon microspheres are determined according to the method described in Example 1. The results are shown in Table 1.
[0165] Example 1-6 Preparation of porous carbon microspheres
[0166] (1) Lignin was dissolved in a sodium hydroxide solution and a microsphere precursor with a particle size Dv50 of 9.4 μm was prepared by spray granulation.
[0167] The preparation method is as follows:
[0168] A lignin solution with a viscosity of 3000-10000 mPa·S is fed into a spray drying device through a feed pump. The feed port temperature of the device is 150-200°C, and the discharge port temperature is 70-120°C. By adjusting the feed rate, a microsphere precursor can be prepared.
[0169] (2) The microsphere precursor is carbonized at 650°C for 2 h in an inert gas atmosphere such as nitrogen to prepare carbon microspheres.
[0170] (3) The carbon microspheres are mixed with sodium hydroxide in a ratio of 1:2, activated at 800°C for 2 h in an inert gas such as nitrogen atmosphere, washed with 3% hydrochloric acid, washed with deionized water to a pH of 5-7, and heat treated at 1000°C for 2 h to obtain porous carbon microspheres that can be used for silicon-carbon negative electrodes. The particle size Dv50, Dv100, pore volume, micropore volume, microporosity and specific surface area of the porous carbon microspheres are determined according to the method described in Example 1. The results are shown in Table 1.
[0171] Example 1-7 Preparation of porous carbon microspheres
[0172] (1) The starch is mechanically granulated to obtain a microsphere precursor with a particle size Dv50 of 9.8 μm. The specific method is as follows:
[0173] S1, adding starch, maleic anhydride and deionized water into a reactor in proportion, stirring at 300 rpm for 1 hour to uniformly mix the raw materials to obtain a starch slurry; wherein the mass ratio of starch, maleic anhydride and deionized water is 1:0.8:2.5;
[0174] S2, heating the starch slurry prepared in S1 to 45°C at a heating rate of 5-10°C / min, and stirring at a constant temperature at 200 rpm for 1-2 hours;
[0175] S3: Fill the reactor with inert gas until the pressure in the reactor reaches 1.5 MPa, and continue stirring for 2 h;
[0176] S4. After the stirring is completed, the reaction solution is spray-dried at 170-190° C. to obtain starch microspheres.
[0177] (2) The microsphere precursor is carbonized at 650°C for 2 h in an inert gas atmosphere such as nitrogen to prepare carbon microspheres.
[0178] (3) The carbon microspheres are mixed with potassium hydroxide in a ratio of 1:2, activated at 800°C for 2 h in an inert gas such as nitrogen atmosphere, washed with 3% hydrochloric acid, washed with deionized water to a pH of 5-7, and then heat treated at 1000°C for 2 h to obtain porous carbon microspheres that can be used for silicon-carbon negative electrodes. The particle size Dv50, Dv100, pore volume, micropore volume, microporosity and specific surface area of the porous carbon microspheres are determined according to the method described in Example 1. The results are shown in Table 1.
[0179] Example 1-8 Preparation of porous carbon microspheres
[0180] (1) A microsphere precursor with a particle size Dv50 of 7.4 μm was prepared by dehydration polymerization of pentose sugar solution (xylose sugar solution).
[0181] The specific method is:
[0182] The pentose and deionized water are mixed into a 5-30% sugar solution, which is heated to 130-200° C. in a high-pressure reactor and kept warm for 1-10 hours. Under this condition, the xylose is dehydrated and polymerized into a microsphere precursor.
[0183] (2) The microsphere precursor is carbonized at 650°C for 2 h in an inert gas atmosphere such as nitrogen to prepare carbon microspheres.
[0184] (3) The carbon microspheres are mixed with potassium hydroxide in a ratio of 1:2, activated at 800°C for 2 h in an inert gas such as nitrogen atmosphere, washed with 3% hydrochloric acid, washed with deionized water to a pH of 5-7, and then heat treated at 1000°C for 2 h to obtain porous carbon microspheres that can be used for silicon-carbon negative electrodes. The particle size Dv50, Dv100, pore volume, micropore volume, microporosity and specific surface area of the porous carbon microspheres are determined according to the method described in Example 1. The results are shown in Table 1.
[0185] Comparative Example 1
[0186] The difference between Comparative Example 1 and Example 1-1 is that no activator is used, and the reaction is directly carried out at 650°C to obtain porous carbon microspheres for silicon-carbon negative electrode, and the particle size Dv50, Dv100, pore volume, micropore volume, microporosity and specific surface area of the carbon microspheres are determined according to the method of Example 1-1. The results are shown in Table 1.
[0187] Comparative Example 2
[0188] The carbon microspheres were prepared according to Example 1 of Chinese patent application CN201810296072.3, and the particle size Dv50, Dv100, pore volume, micropore volume, microporosity and specific surface area of the carbon microspheres were measured according to the method of Example 1-1. The results are shown in Table 1.
[0189] Comparative Example 3 Coconut shell carbonized material (non-microsphere)
[0190] (1) The dried coconut shell is ground into powder by mechanical pulverization to obtain a precursor with a particle size Dv50 of 6.8 μm.
[0191] (2) The precursor is carbonized at 650° C. for 2 h in an inert gas atmosphere such as nitrogen to prepare a carbonized coconut shell material.
[0192] (3) The carbonized material is mixed with potassium hydroxide in a ratio of 1:2, activated at 800°C for 2 h in an inert gas such as nitrogen atmosphere, washed with 3% hydrochloric acid, washed with deionized water to a pH of 5-7, and heat treated at 1000°C for 2 h to obtain porous carbon that can be used for silicon-carbon negative electrode. The particle size Dv50, Dv100, pore volume, micropore volume, microporosity and specific surface area of the porous carbon are determined according to the method described in Example 1. The results are shown in Table 1.
[0193] Table 1 Performance parameters of microspheres
[0194]
[0195]
[0196] Example 2
[0197] Example 2-1 Preparation of silicon-carbon negative electrode material
[0198] The porous carbon microspheres prepared in Example 1-1 were used as carriers, and silicon-containing gas was used to deposit inside the porous carbon microspheres to prepare silicon-carbon negative electrode materials. The silicon content is shown in Table 2.
[0199] The silicon-containing gas is silane, the processing temperature during the silicon deposition is 600° C., the processing time during the silicon deposition is 10 hours, and the silicon content is 48.6% by mass in the silicon-carbon negative electrode, wherein the silicon content is determined by TGA method.
[0200] Example 2-2 Preparation of silicon-carbon negative electrode material
[0201] The same operation as Example 2-1 was performed, except that the porous carbon microspheres described in Example 1-2 were used as carriers, and the silicon content was as shown in Table 2.
[0202] Example 2-3 Preparation of silicon-carbon negative electrode material
[0203] The same operation as Example 2-1 was performed, except that the porous carbon microspheres described in Example 1-3 were used as carriers. The silicon content was as shown in Table 2.
[0204] Example 2-4 Preparation of silicon-carbon negative electrode material
[0205] The same operation as Example 2-1 was performed, except that the porous carbon microspheres described in Example 1-4 were used as carriers, and the silicon content was as shown in Table 2.
[0206] Example 2-5 Preparation of silicon-carbon negative electrode material
[0207] The same operation as Example 2-1 was performed, except that the porous carbon microspheres described in Example 1-5 were used as carriers, and the silicon content was as shown in Table 2.
[0208] Example 2-6 Preparation of silicon-carbon negative electrode material
[0209] The same operation as Example 2-1 was performed, except that the porous carbon microspheres described in Example 1-6 were used as carriers, and the silicon content was as shown in Table 2.
[0210] Example 2-7 Preparation of silicon-carbon negative electrode material
[0211] The same operation as Example 2-1 was performed, except that the porous carbon microspheres described in Example 1-7 were used as carriers, and the silicon content was as shown in Table 2.
[0212] Example 2-8 Preparation of silicon-carbon negative electrode material
[0213] The same operation as Example 2-1 was performed, except that the porous carbon microspheres described in Example 1-8 were used as carriers, and the silicon content was as shown in Table 2.
[0214] Comparative Example 4 Preparation of Silicon Carbon Anode Material
[0215] The same operation as Example 2-1 was performed, except that the porous carbon microspheres described in Comparative Example 1 were used as carriers, and the silicon content was as shown in Table 2.
[0216] Comparative Example 5 Preparation of Silicon Carbon Anode Material
[0217] The same operation as Example 2-1 was performed, except that the porous carbon microspheres described in Comparative Example 2 were used as carriers, and the silicon content was as shown in Table 2.
[0218] Comparative Example 6 Preparation of Silicon Carbon Anode Material
[0219] The same operation as Example 2-1 was performed, except that the carbon microspheres described in Comparative Example 3 were used as carriers, and the silicon content was as shown in Table 2.
[0220] Table 2 Silicon content of different silicon-carbon negative electrode materials
[0221] Silicon Carbon Anode Material Silicon content (by weight) % Example 2-1 The prepared in Example 1-1 48.6 Example 2-2 The prepared in Example 1-2 48.9 Example 2-3 The prepared in Example 1-3 51.2 Embodiment 2-4 The prepared in Example 1-4 47.3 Embodiment 2-5 The prepared in Example 1-5 47.8 Embodiment 2-6 The prepared 51.1 Embodiment 2-7 The prepared 48.9 Embodiment 2-8 The prepared 50.3 Comparative Example 4 The obtained 23.4 Comparative Example 5 The obtained 26.1 Comparative Example 6 The obtained 47.2
[0222] Example 3
[0223] Example 3-1 Preparation of lithium battery
[0224] The silicon-carbon negative electrode material prepared in Example 2-1 was mixed with SP, SBR, and CMC in a mass ratio of 80:10:5:5, and the mixture was mixed into a slurry using ultrapure water as a solvent, and evenly coated on a copper foil, and vacuum dried at 120°C for 12 hours to obtain a battery electrode; then a lithium sheet was used as a counter electrode, a four-component mixed solvent of LiPF6 with a molar concentration of 1 mol / L (according to the mass ratio of EC:DMC:EMC:FEC=3:4:2:1) was used as an electrolyte, and a polypropylene film was used as a diaphragm to assemble into a CR2032 button half-cell in a vacuum glove box.
[0225] First coulombic efficiency test: the button half-cell was discharged to 5mV at a constant current of 0.1C, and charged to 1.5V at a constant current of 0.1C. Similarly, it was discharged to 5mV at a constant current of 0.1C, and charged to 1.5V at a constant current of 0.1C. At this time, the first cycle discharge capacity C1 (mAh / g) was recorded, and the first coulombic efficiency (%) was calculated. The first cycle discharge capacity C1 and the first coulombic efficiency are shown in Table 3.
[0226] Example 3-2 Preparation of lithium battery
[0227] The same operation as Example 3-1 was performed, except that the silicon-carbon negative electrode material described in Example 2-2 was used to prepare the lithium battery. The first cycle discharge capacity C1 and the first coulombic efficiency are shown in Table 3.
[0228] Example 3-3 Preparation of lithium battery
[0229] The same operation as Example 3-1 was performed, except that the silicon-carbon negative electrode material described in Example 2-3 was used to prepare the lithium battery. The first cycle discharge capacity C1 and the first coulombic efficiency are shown in Table 3.
[0230] Example 3-4 Preparation of lithium battery
[0231] The same operation as Example 3-1 was performed, except that the silicon-carbon negative electrode material described in Example 2-4 was used to prepare the lithium battery. The first cycle discharge capacity C1 and the first coulombic efficiency are shown in Table 3.
[0232] Example 3-5 Preparation of lithium battery
[0233] The same operation as Example 3-1 was performed, except that the silicon-carbon negative electrode material described in Example 2-5 was used to prepare the lithium battery. The first cycle discharge capacity C1 and the first coulombic efficiency are shown in Table 3.
[0234] Example 3-6 Preparation of lithium battery
[0235] The same operation as Example 3-1 was performed, except that the silicon-carbon negative electrode material described in Example 2-6 was used to prepare the lithium battery. The first cycle discharge capacity C1 and the first coulombic efficiency are shown in Table 3.
[0236] Example 3-7 Preparation of lithium battery
[0237] The same operation as Example 3-1 was performed, except that the silicon-carbon negative electrode material described in Example 2-7 was used to prepare the lithium battery. The first cycle discharge capacity C1 and the first coulombic efficiency are shown in Table 3.
[0238] Example 3-8 Preparation of lithium battery
[0239] The same operation as Example 3-1 was performed, except that the silicon-carbon negative electrode material described in Example 2-8 was used to prepare the lithium battery. The first cycle discharge capacity C1 and the first coulombic efficiency are shown in Table 3.
[0240] Comparative Example 7 Preparation of lithium battery
[0241] The same operation as Example 3-1 was performed, except that the silicon-carbon negative electrode material described in Comparative Example 4 was used to prepare the lithium battery. The first cycle discharge capacity C1 and the first coulombic efficiency are shown in Table 3.
[0242] Comparative Example 8 Preparation of lithium battery
[0243] The same operation as Example 3-1 was performed, except that the silicon-carbon negative electrode material described in Comparative Example 5 was used to prepare the lithium battery. The first cycle discharge capacity C1 and the first coulombic efficiency are shown in Table 3.
[0244] Comparative Example 9 Preparation of lithium battery
[0245] The same operation as Example 3-1 was performed, except that the silicon-carbon negative electrode material described in Comparative Example 6 was used to prepare the lithium battery. The first cycle discharge capacity C1 and the first coulombic efficiency are shown in Table 3.
[0246] Table 3 Performance parameters of lithium batteries prepared with different silicon-carbon negative electrode materials
[0247]
[0248] As can be seen from the above table, when the microspheres prepared by the method described in the present application are prepared into silicon-carbon negative electrode materials and prepared into batteries, the first coulombic efficiency of the battery is high and the capacity is also high. For Comparative Examples 1 and 2, since no activator is used, when the obtained microspheres are prepared into silicon-carbon negative electrodes and then prepared into batteries, the first coulombic efficiency and capacity of the batteries are low, indicating that the use of an activator for activation has a significant effect on the pore volume, micropore volume, and specific surface area of the microspheres. Therefore, when preparing the silicon-carbon negative electrode, due to the differences in these parameters, the silicon-containing gas is deposited in the pores of these microspheres, and the resulting silicon-carbon negative electrode materials are also significantly different. When the silicon-carbon negative electrode material is used to prepare a battery, the performance of the resulting battery is also significantly different.
[0249] For Comparative Example 3, since the carbon source material used is different, the material prepared is not a microspherical material (granular material). When the two are prepared into silicon-carbon negative electrode materials, the microspheres are subjected to more uniform force direction when silicon expands, and the strength is higher, and they are not easily broken due to the expansion of silicon. This is similar to the nearly spherical graphite material in the battery negative electrode, which results in better battery performance when prepared into a battery.
[0250] The above is only the preferred embodiment of the present application, and does not limit the present application in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present application without departing from the technical solution of the present application still falls within the protection scope of the technical solution of the present application.
Claims
1. A porous carbon microsphere for a silicon-carbon negative electrode, wherein the microsphere is spherical or nearly spherical, and the microporosity of the microsphere is 70-99%.
2. The porous carbon microspheres according to claim 1, wherein The pore volume of the microspheres is 0.3-1.5 cm 3 / g, micropore volume is 0.2-1.5cm 3 / g.
3. The porous carbon microspheres according to claim 1 or 2, wherein: The specific surface area of the microspheres is 700-3000m 2 / g; Preferably, the particle size Dv50 of the microspheres is 1-10 μm, and Dv100 is less than 30 μm.
4. A method for preparing porous carbon microspheres for silicon-carbon negative electrode, comprising: The carbon source is polymerized to obtain a carbon microsphere precursor; The carbon microsphere precursor is subjected to carbonization reaction and activation reaction to obtain porous carbon microspheres.
5. The method according to claim 4, wherein: The carbon source is selected from one or more of phenolic resin, furan resin, furanone resin, lignin, cellulose, starch, pentose, hexose, molasses, asphalt, mesophase microspheres and starch; Preferably, the polymerization is selected from one of emulsion polymerization, thermal polycondensation, dehydration polymerization, mechanical granulation, spray granulation and hydrothermal carbonization; Preferably, the temperature of the carbonization reaction is 400-700°C, and / or the time of the carbonization reaction is 0.5-5h; Preferably, the activation reaction temperature is 700-900°C, and / or The activation reaction time is 0.5-2h, and / or The activator used in the activation reaction is selected from one or more of potassium hydroxide, sodium hydroxide, potassium carbonate, sodium carbonate, potassium bicarbonate and sodium bicarbonate; Preferably, the porous carbon microspheres are the porous carbon microspheres according to any one of claims 1 to 3.
6. Use of the porous carbon microspheres according to any one of claims 1 to 3 or the porous carbon microspheres prepared by the method according to any one of claims 4 to 5 in silicon-carbon negative electrode materials.
7. A silicon-carbon negative electrode material, which is prepared by a method comprising the following steps: Using the porous carbon microspheres according to any one of claims 1 to 3 or the porous carbon microspheres prepared by the method according to any one of claims 4 to 5 as carriers to deposit silicon to obtain a silicon-carbon negative electrode material; Preferably, the silicon deposition is obtained by adsorption, decomposition and deposition of silicon-containing gas in the pores of porous carbon microspheres; Preferably, the silicon-containing gas is silane or methylsilane, and / or The processing temperature during silicon deposition is 300-900°C, and / or The processing time of the silicon deposition is 1-24 hours, and / or Calculated by mass percentage in the silicon-carbon negative electrode, silicon accounts for 20-75%.
8. A method for preparing a silicon-carbon negative electrode material, comprising: Using the porous carbon microspheres according to any one of claims 1 to 3 or the porous carbon microspheres prepared by the method according to any one of claims 4 to 5 as carriers to deposit silicon to obtain a silicon-carbon negative electrode material; Preferably, the silicon deposition is obtained by adsorption, decomposition and deposition of silicon-containing gas in the pores of porous carbon microspheres; Preferably, the silicon-containing gas is silane or methylsilane, and / or The processing temperature during silicon deposition is 300-900°C, and / or The processing time of the silicon deposition is 1-24 hours, and / or Calculated by mass percentage in the silicon-carbon negative electrode, silicon accounts for 20-75%.
9. Use of the silicon-carbon negative electrode material according to claim 7 or the silicon-carbon negative electrode material prepared by the method according to claim 8 in lithium-ion batteries.
10. A lithium-ion battery comprising the silicon-carbon negative electrode material according to claim 7 or the silicon-carbon negative electrode material prepared by the method according to claim 8.
Citation Information
Patent Citations
Phenol formaldehyde resin carbon micro-sphere preparation method and application of phenol formaldehyde resin carbon micro-sphere in lithium ion battery electrode
CN103545520A
Porous carbon microsphere, preparation method and lithium ion battery negative electrode material
CN103545523A
Preparation method of submicron porous carbon bead
CN103871756A
Activated mesocarbon microbeads, preparation method thereof and supercapacitor
CN104098078A
Lithium ion battery anode material with high specific capacity and preparation method of lithium ion battery anode material
CN109809385A
Cited By
Silicon-carbon negative electrode material based on spherical starch porous carbon and preparation method of silicon-carbon negative electrode material
CN120039880A
A silicon-carbon negative electrode material based on spherical starch porous carbon and its preparation method
CN120039880B
Silicon-carbon negative electrode material and preparation method and application thereof
CN120784308A
Activated carbon microspheres, and methods of making and using the same
CN122685062A